Development of Android-Based Management Information System Application for Student Final Project Services (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The final project service system in the Industrial Engineering Study Program at Universitas Pembangunan Nasional "Veteran" East Java is designed to support the administrative operations performed by both lecturers and students. However, the current system still relies on conventional methods such as Google Forms, email, and WhatsApp, which complicate the processes of submitting pre-proposals, proposal seminars, and result seminars. Therefore, a management information system is needed to integrate all final project service processes into a single application. The objective of this study is to develop a design for a final project management application for students of the Industrial Engineering Study Program at UPN "Veteran" East Java, based on Android. The application is designed using the Rapid Application Development (RAD) method, which consists of three stages: Requirements Planning, Design Workshop, and Implementation. The system design includes the use of context diagrams, Entity Relationship Diagrams (ERD), and Data Flow Diagrams (DFD) to illustrate the data flow. Verification and validation tests show that all features of the application function as intended. This application is expected to facilitate and streamline the management of final project submissions, making the service more effective and efficient.